Propriedade intelectual e as indústrias criativas: cultura digital, regulamentação e as licenças públicas - Carvalho, Juliano Maurício de [UNESP]; Lopes, Giovana Franzolin; Zambon, Pedro Santoro (My University, 2014)
When we think of a transposition from a traditional culture industry to the new coherence of the creative industries, a number of new parallel discussions arises, encircled by the reconfiguration of the value chain of such industries and, not only, but also due to a change on creation coherence of a product whose most valuable input is creativity. Therefore, as a mechanism through which such creativity is valued, the intellectual property becomes one of the key elements of this debate, mainly in a world where the coherence of distribution transcends the physical copies towards the digitization of content. From this initial debate, the present article seeks to weave the main relations between the theme of creative industries and the intellectual property, describing the adversities of a deficient regulation and its consequences on the creative industries production, indicating the existing alternatives and questioning the balance between two forces: the collective and the individual rights.

Quando pensada uma transposição de uma indústria cultural tradicional para a nova lógica das indústrias criativas, surge uma série de questionamentos paralelos, abarcados pela reconfiguração da cadeia de valor destas indústrias e, não somente, mas também pela mudança da lógica da criação de um produto cujo insumo mais valioso é a criatividade. Por consequência, como mecanismo pelo qual se valora comercialmente tal criatividade, a propriedade intelectual se torna um dos elementos-chave desses questionamentos, principalmente em um mundo onde a lógica da distribuição transcende a cópia física para a digitalização do conteúdo. Partindo desse debate inicial, este artigo busca tecer as principais relações entre a temática das indústrias criativas e a propriedade intelectual, descrevendo os percalços de uma regulamentação falha e suas consequências na produção das indústrias criativas, indicando as alternativas existentes e questionando o equilíbrio entre duas forças: o direito coletivo e o direito individual.
Keywords: Intellectual property; Copyright; Copyleft; Creative Commons; Creative industries; Propriedade intelectual; Copyright; Copyleft; Creative Commons; Indústrias criativas